Prevalence of Ideal Cardiovascular Health and Its Association with Cognitive Function in Older Adults: The Chilean National Health Survey (2009-2010) (2018)
Health behaviors and risk factors are independently related with cognitive function in older adults. This study aimed at examining the prevalence and relationship between cognitive function and a number of ideal cardiovascular health (CVH) metrics in older adults from the 2009 to 2010 Chilean National Health Survey. Data from 460 older adults (mean age 73.5 years old, 59.3% women) from the 2009 to 2010 Chilean Health Survey were analyzed. Ideal CVH was defined as meeting the ideal levels of the following components: four behaviors (smoking, body mass index, physical activity, and diet adherence) and three factors (total cholesterol, blood pressure, and fasting glucose). Older adults were grouped into three categories according to their number of ideal CVH metrics: ideal (5-7 metrics), intermediate (3-4 metrics), and poor (0-2 metrics). Cognitive function was assessed by using the modified Mini-Mental Status Examination (mMMSE). Of the 460 participants, 2% had 0 ideal metrics, 11.3% had 1, 23.9% had 2, 32.2% had 3, 20.7% had 4, 9.6% had 5, 0.4% had 6, and 0% had 7. Cognitive function was greater in older adults who met the ideal smoking, physical activity, and fasting blood glucose criteria. Logistic regression analysis suggested that ideal physical activity (Odds Ratio [OR] = 0.411 95% confidence interval [95% CI], 0.209-0.807) and smoking (OR = 0.429 95% CI, 0.095-0.941) behaviors reduced the likelihood of cognitive impairment. Moreover, compared with a poor profile (0-2 metrics), an intermediate (3-4 metrics) (OR = 0.221 95% CI, 0.024-0.911) and ideal CVH profile (5-7 metrics) (OR = 0.106 95% CI, 0.013-0.864) reduced the likelihood of cognitive impairment. We found that intermediate and ideal profiles were associated with a similarly low prevalence of cognitive impairment in Chilean older adults. © Copyright 2018, Mary Ann Liebert, Inc. 2018.